Efficiency Estimates and Rankings Employing Data Envelopment and Stochastic Frontier Analyses: Evaluating the Management of U.S. Public Colleges - Sav, G. Thomas (Information Management and Business Review, 2012)
This paper estimates and compares operating efficiencies of publicly owned associate degree granting colleges in the United States using data envelopment analysis (DEA) and stochastic frontier analysis (SFA). Comparisons are based on panel data for 698 colleges over four academic years, 2005-09. Included are both constant and variable returns to scale DEA estimates along with half and truncated normal inefficiency SFA estimates. The values 0.56 vs. 0.45 represent the largest mean DEA-SFA efficiency differential. DEA results indicate that 13% of colleges are fully (100%) efficient while SFA puts that percentage at only 1.7%. Comparisons of rankings based on efficiency performance generated a weak 0.65 correlation. Encouragingly, despite the financial turmoil initiated by the global crisis, the findings indicate that colleges have managed large efficiency gains over the four-year period. By 2008-09, DEA estimated efficiency increased to approximately 60%. Given continuing reductions in higher education public funding and increasing interest in public management reforms, the results should be of both managerial and public policy interest.